MULTIPLIKASI TUNAS, PERAKARAN DAN AKLIMATISASI TANAMAN SAMBANG NYAWA (Gynura procumbens) - Kristina, N. Nova; Sirait, Nursalam; Bermawie, Nurliani (Pusat Penelitian dan Pengembangan Perkebunan, 2005)
Shoots Multiplication, Rooting, and Acclimatization of Gynura procumbensThe research was performance to obtain shoots multiplication, rooting and acclimati-zation of Gynura procumbens was conducted January 2004 to May 2005 at the Laboratory of Tissue Culture of Gremplasm and Breeding Division. This research was conducted within two steps, i.e. 1) : Shoots multiplication in : MS + BA (0; 0,1; 0,3 and 0,5 ) mg/l; 2) rooting and acclimatization. Explants were culture on rooting medium MS + IAA (0,1; 0,3); MS + IBA (0,1; 0,3) or NAA (0,1 and 0,3) mg/l. Acclimatization were performanced on the two kinds of media i.e. dung manure + soil (1 : 1) or husk + soil (1 : 1). Rooting and shoots multiplication were arranged in completely randomized design, with 10 replications and 2 explants for each bottle. Acclimatization was arranged in randomized-block design with 10 replications and 1 plantlet for each treatment. The results showed the best medium for multiplication shoot was MS-free hormone with 5,4 shoots, 2 months after cultured. The highest number of roots was obtained in NAA 0,1 mg/l with 9,3/plantet. MS + IBA 0,3 mg/l give the longest roots (9,58 cm) and IAA 0,1 mg/l the highest number of leaf (12/plantet). Interaction between the source medium and acclimatization medium was observed however, there was no significantly difference between IAA 0,1 mg/l and IBA 0,1 mg/l in number of shoots and long shoots (5,2 and 5,01 cm).